Morbidity Profile and Substance use among the Elderly Tribal and Non Tribal Population of the Imphal East District of Manipur, India - , Sonia Yengkokpam; , Natasha R. Marak; , Pavana Kumar; , Sunanda Nongthombam (Archives of Current Research International, 2024)
This study employs correlation and regression analysis to compile a comprehensive profile of morbidity and psychoactive substance use among the elderly tribal and non-tribal populations in the Imphal East district of Manipur. By identifying prevalent health issues such as hypertension, osteoporosis and diabetes mellitus, alongside shared practices of alcohol consumption and chewing tobacco, the research sheds light on critical health concerns and behavioral patterns affecting this demographic. The findings provide valuable insights for targeted interventions and policy formulation to address the pressing health challenges faced by the elderly in this region. Through a thorough assessment of morbidity and substance use, this study contributes to a deeper understanding of the health dynamics within the elderly population, paving the way for informed decision-making and improved healthcare strategies tailored to the needs of this vulnerable demographic group.